2023
DOI: 10.1021/acsphotonics.3c00907
|View full text |Cite
|
Sign up to set email alerts
|

Laser-Written Tunable Liquid Crystal Aberration Correctors

Alec Xu,
Camron Nourshargh,
Patrick S. Salter
et al.

Abstract: In this Article, we present a series of novel laser-written liquid crystal (LC) devices for aberration control for applications in beam shaping or aberration correction through adaptive optics. Each transparent LC device can correct for a chosen aberration mode with continuous greyscale tuning up to a total magnitude of more than 2π radians phase difference peak to peak at a wavelength of λ = 660 nm. For the purpose of demonstration, we present five different devices for the correction of five independent Zern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…The principle behind this approach is illustrated in Figure 1. Recently, in Xu et al [13], we demonstrated the versatility of such an approach, replicating one Zernike mode from each of the first five non-trivial orders of Zernike modes, with our tilt device demonstrating a root mean square (RMS) phase error of no more than 0.27 rad for all amplitudes.…”
Section: Introductionmentioning
confidence: 89%
“…The principle behind this approach is illustrated in Figure 1. Recently, in Xu et al [13], we demonstrated the versatility of such an approach, replicating one Zernike mode from each of the first five non-trivial orders of Zernike modes, with our tilt device demonstrating a root mean square (RMS) phase error of no more than 0.27 rad for all amplitudes.…”
Section: Introductionmentioning
confidence: 89%
“…Recently, in Xu et al 10 , we were able to further demonstrate that by continuously varying the polymerization depth within the LC layer, we could even successfully recreate Zernike polynomials and generate continuously tunable aberration correction devices. These results were very promising, demonstrating the high versatility and applicability of this technique.…”
Section: Introductionmentioning
confidence: 90%
“…In the present paper, we tackle the challenge posed by the commonly occurring spherical aberration by creating a new aberration correction device. The spherical mode corrector device presented is significantly larger than the correctors described in Xu et al 10 , at 16 times the area, with a large total diameter of 1000 μm, which would allow the device to be much more easily integrated into practical optical paths. Furthermore, a demonstration of devices of this size indicates that the device size is not limited by the manufacturing process.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Stimuli-responsive polymer materials like hydrogels, magnetic polymers, and liquid crystal (LC) networks (LCNs) and elastomers (LCEs) (jointly termed liquid crystal polymers (LCPs)) capable of externally triggered shape deformations can be utilized to make 3D micro-objects that change their configuration in time . Many applications of such systems, commonly termed 4D, are envisioned, including targeted drug delivery, cell manipulation, microsurgery, , smart surfaces for haptic technologies or controlled wettability, microrobotics, , microassembly, , photonics, and advanced microfluidics …”
Section: Introductionmentioning
confidence: 99%